GESTÃO DE ORGANIZAÇÕES DE APRENDIZAGEM: UM ESTUDO SOBRE AS ORGANIZAÇÕES DO TERCEIRO SETOR CRIADORAS DE FRANQUIAS SOCIAIS - Gonzaga, Adriana Motta (2009)
This study aims at understanding of the management tool known as Social Franchise, for the purpose of investigating the operation of postage meters and compare them to the characteristics of learning organizations - the learning organizations discussed by Peter Senge. The dissertation is an approach from the perspective of the franchisor on the network formed around the social franchising and the formation of an extensive capillary capable of providing exchange of experience critical to their success and survival. Thus, there was initially a literature emphasizing questions about the Welfare State and the relations between State, market and society have created a new social sector, or public or private - the Third Sector. From this analytical tool, the focus turns to the realization of exploratory research in social projects, which proved to be essentially qualitative. The exploratory search was concentrated in the chance that the franchisor is to create an environment conducive to the development of learning organizations, showing that from a combination of both is determined by the success of his management.